Evaluating the Impact of Targeted Shoulder Exercises on Shoulder Impingement Syndrome: A Comprehensive Case Study - Nur Ainah Mohd Shipah; Noor Izzati Azhar (Asian Journal of Medicine & Health Sciences, 2024)
Shoulder impingement syndrome (SIS) is a common cause of shoulder pain, especially among the elderly, particularly in women. SIS significantly affects shoulder function in daily activities and work quality. This case study focused on a 57-year-old female who experienced moderate to highintensity shoulder pain and limited range of motion of left shoulder joint after falling at home. The objective was to alleviate pain and improve shoulder function through shoulder exercises. Mobility exercises for the shoulder joint and strengthening exercises for the serratus anterior, rhomboid and trapezius muscle were administered, resulting in reduced pain and increased range of motion. The study demonstrated that shoulder exercises had a beneficial effect on patient with SIS. Addressing the specific muscle weaknesses is crucial to enhancing overall shoulder function. This research highlights the importance of strengthening exercises for shoulder muscles as management strategies in SIS.